Hovering by Gazing: A Novel Strategy for Implementing Saccadic Flight-Based Navigation in GPS-Denied Environments. (23rd April 2014) - Manecy, Augustin; Marchand, Nicolas; Viollet, Stéphane
Hovering flies are able to stay still in place when hovering above flowers and burst into movement towards a new object of interest (a target). This suggests that sensorimotor control loops implemented onboard could be usefully mimicked for controlling Unmanned Aerial Vehicles (UAVs). In this study, the fundamental head-body movements occurring in free-flying insects was simulated in a sighted twin-engine robot with a mechanical decoupling inserted between its eye (or gaze) and its body. The robot based on this gaze control system achieved robust and accurate hovering performances, without an accelerometer, over a ground target despite a narrow eye field of view (±5°). The gaze stabilization strategy validated under Processor-In-the-Loop (PIL) and inspired by three biological Oculomotor Reflexes (ORs) enables the aerial robot to lock its gaze onto a fixed target regardless of its roll angle. In addition, the gaze control mechanism allows the robot to perform short range target to target navigation by triggering an automatic fast "target jump" behaviour based on a saccadic eye movement.